1989
DOI: 10.1159/000248100
|View full text |Cite
|
Sign up to set email alerts
|

Paget’s Disease of the Nipple Resembling an Acantholytic Disease on Microscopic Examination

Abstract: Two biopsies of an erosive lesion of the nipple had an appearance of an acantholytic disease without showing malignant cells. Only a third biopsy through the nipple with removal of a larger portion revealed some nests of atypical, large cells with clear cytoplasm, typical of Paget’s disease. Immunohistochemical findings with carcinoem-bryonic antigen confirmed the diagnosis of Paget’s disease of the nipple. This is the first case of Paget’s disease which shows extensive acantholysis on microscopic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Two isolated reports in the literature describe prominent acantholysis in PD; in one, the diagnosis was initially rendered as pemphigus vulgaris and only a third biopsy of an erosive lesion on the nipple established the correct diagnosis; however, there is no mention of any anaplastic appearance of the cells. In the other case where there was no underlying mass, upon further investigations, the diagnosis of PD was established 8,9 . Therefore, presence of marked anaplasia and acantholysis may not be codependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two isolated reports in the literature describe prominent acantholysis in PD; in one, the diagnosis was initially rendered as pemphigus vulgaris and only a third biopsy of an erosive lesion on the nipple established the correct diagnosis; however, there is no mention of any anaplastic appearance of the cells. In the other case where there was no underlying mass, upon further investigations, the diagnosis of PD was established 8,9 . Therefore, presence of marked anaplasia and acantholysis may not be codependent.…”
Section: Discussionmentioning
confidence: 99%
“…In the other case where there was no underlying mass, upon further investigations, the diagnosis of PD was established. 8,9 Therefore, presence of marked anaplasia and acantholysis may not be codependent. One of our cases developed PD in the nipple 5 years after lumpectomy, despite negative surgical margins and no vascular or metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Wolf et al reported Paget's disease that resembled pemphigus in a woman that was unsuccessfully treated for 8 months with an erosive, oozing lesion on her nipple (6). Initially pathologic evaluations of the localized tissue specimens from the areolar borders were suggestive of pemphigus, but immunohistochemical analyses proved to be negative.…”
Section: Discussionmentioning
confidence: 99%
“…16A-B), which likely constitutes a nonspecific change in the epidermis, resulting in loss of intercellular adhesions. 74,75 ,…”
Section: Histopathologymentioning
confidence: 99%